A Review of Drug Design Techniques Assisted by Computers to Combat Diabetes - Mohd. Wasiullah; Piyush Yadav; Neeraj Maurya; Satish Kumar Yadav; Akash Mishra (Emerging Trends in Personalized Medicines, 2024)
Diabetes mellitus is a global health concern characterized by chronic hyperglycemia and associated complications. The creation of innovative medicines with enhanced efficacy and safety profiles continues to be a top focus, notwithstanding improvements in treatment. A useful method in drug development, computer-aided drug design (CADD) makes it easier to identify possible therapeutic candidates and optimise lead molecules. An extensive synopsis of CADD tactics used in the fight against diabetes is given in this review. It explores virtual screening, molecular docking, pharmacophore modeling, and molecular dynamics simulations, highlighting their applications in identifying novel targets, lead compounds, and multi-target drug combinations. Additionally, it discusses challenges such as data integration, experimental validation, and ethical considerations, along with opportunities for future research, including the integration of artificial intelligence, high-throughput screening, and personalized medicine approaches. This review underscores the potential of CADD to accelerate the discovery of innovative therapeutics for diabetes management, ultimately improving patient outcomes and addressing unmet clinical needs.
Keywords: Computer-aided drug design (CADD); Diabetes mellitus; Drug discovery; Molecular dynamics simulations; Personalized medicine; Pharmacophore modelling; Therapeutic targets; Virtual screening; artificial intelligence; molecular docking